2022
DOI: 10.1002/er.8211
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated copper phthalocyanine as an electron transport material in perovskite solar cell

Abstract: Summary The state‐of‐art charge transport materials, TiO2 and Spiro‐OMeTAD suffer from various drawbacks such as instability, lengthy fabrication procedure and low charge mobilities. In this paper, we have studied copper phthalocyanine (CuPc) and halogen‐substituted copper phthalocyanine (X16CuPc; X = F, Cl, Br, I) through density functional theory (DFT) and determined their ground state properties, excited state properties and solubility in DMSO (widely used solvent in the fabrication of perovskite solar cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 74 publications
0
20
0
Order By: Relevance
“…In a recent study, CuPc and F 16 CuPc were studied as hole and electron transport layers in an MAPI 3 -based PSC device, respectively, through DFT calculations and compared to the state-of-art charge transport materials TiO 2 and spiro-OMeTAD, suggesting that better efficiency can be achieved for the Pc-based device. 149 The device simulation study showed that an FF of 79.01% and PCE of 22.30% can be expected for this PSC device. In 2022, iron(II)-2,9,16,23-tetraamino-phthalocyanine (FeTAP) (73) was used as an additive inside a mixed-halide perovskite layer to passivate the defects at the surface and grain boundaries through the formation of strong bonds between the unsaturated Pb 2+ ions and N-H moieties.…”
Section: Pc Complexes Using As Additives In Perovskite Layermentioning
confidence: 85%
“…In a recent study, CuPc and F 16 CuPc were studied as hole and electron transport layers in an MAPI 3 -based PSC device, respectively, through DFT calculations and compared to the state-of-art charge transport materials TiO 2 and spiro-OMeTAD, suggesting that better efficiency can be achieved for the Pc-based device. 149 The device simulation study showed that an FF of 79.01% and PCE of 22.30% can be expected for this PSC device. In 2022, iron(II)-2,9,16,23-tetraamino-phthalocyanine (FeTAP) (73) was used as an additive inside a mixed-halide perovskite layer to passivate the defects at the surface and grain boundaries through the formation of strong bonds between the unsaturated Pb 2+ ions and N-H moieties.…”
Section: Pc Complexes Using As Additives In Perovskite Layermentioning
confidence: 85%
“…The charge carrier hopping is facilitated by lower values of reorganization energies, as proposed by the Marcus theory [41] that is, lower the values of reorganization energies, better is the carrier hoping and easier the charge transport. An efficient HTL should have a low value of hole reorganization energy ( λ hole ) to aid the flow of holes and at the same time have a high value of electron reorganization energy ( λ ele ) to hinder the flow of electrons [10]. Likewise, an efficient ETL should have a low value of electron reorganization energy ( λ ele ) to aid the flow of electrons and at the same time have a high value of hole reorganization energy ( λ hole ) to hinder the flow of holes [10].…”
Section: Resultsmentioning
confidence: 99%
“…An efficient HTL should have a low value of hole reorganization energy ( λ hole ) to aid the flow of holes and at the same time have a high value of electron reorganization energy ( λ ele ) to hinder the flow of electrons [10]. Likewise, an efficient ETL should have a low value of electron reorganization energy ( λ ele ) to aid the flow of electrons and at the same time have a high value of hole reorganization energy ( λ hole ) to hinder the flow of holes [10]. It is observed from Table 2 that the λ hole of P3CPenT is low and the λ ele is higher indicating that P3CPenT aids the hole transport and suppress the electron transport.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations